SLC31A1 promotes chemoresistance through inducing CPT1A-mediated fatty acid oxidation in ER-positive breast cancer - Xudong Li; Jingjing Ge; Mengdi Wan; Tongtong Feng; Xiaoqian Li; Haibo Zhang; Zhangyan Wang; Yongsheng Gao; Meiting Chen; Fei Pan (Neoplasia: An International Journal for Oncology Research)
Over 60% of breast cancer cases are diagnosed with estrogen-receptor (ER) positive. Tamoxifen (TAM), a commonly employed medication for ER-positive breast cancer, often yields suboptimal therapeutic outcomes due to the emergence of TAM resistance, leading to the recurrence and a poor prognosis. The copper transporter, solute carrier family 31 member 1 (SLC31A1), has been associated with tumor aggressiveness and unfavorable outcomes in various types of tumors. In our current study, we found high expression of SLC31A1 that predicted poor survival in patients with breast cancer. Significantly, ER-positive breast cancer tissues in patients with recurrence post-TAM treatment exhibited considerably stronger SLC31A1 expression levels. In vitro experiments verified that TAM-resistant ER-positive breast cancer cell lines expressed notably higher SLC31A1 levels compared to the parental cell lines. Of great significance, SLC31A1 depletion notably rescued TAM sensitivity in chemoresistant ER-positive breast cancer cells, as demonstrated by the attenuated cell proliferative and invasive capabilities. Conversely, promoting SLC31A1 significantly facilitated the proliferation and invasion of wild-type breast cancer cells. Subsequently, we detected reduced copper levels in TAM-resistant breast cancer cells with SLC31A1 depletion. Mechanistically, we observed that in chemoresistant breast cancer cell lines, SLC31A1 knockdown resulted in a substantial decrease in the expression of carnitine palmitoyltransferase 1A (CPT1A), a rate-limiting enzyme of fatty acid oxidation (FAO). RNA-Seq analysis indicated that FAO might be implicated in SLC31A1-mediated breast cancer progression. CPT1A was also overexpressed in TAM-resistant breast cancer cells, accompanied by enhanced FAO rates and ATP levels. Suppressing CPT1A significantly enhanced the chemosensitivity of TAM-resistant breast cancer cells in response to TAM treatments. Intriguingly, copper exposure dose-dependently increased CPT1A expression in chemoresistant breast cancer cells, but this could be abolished upon SLC31A1 knockdown, along with enhanced apoptosis, which elucidated that copper uptake contributed to CPT1A expression. Furthermore, SLC31A1 overexpression significantly augmented CPT1A expression in parental breast cancer cells, accompanied by facilitated copper levels, FAO rates, and ATP levels, while being notably diminished upon CPT1A suppression. Finally, our in vivo studies confirmed that SLC31A1 deficiency re-sensitized TAM-resistant breast cancer cells to TAM treatment and abolished tumor growth. Collectively, all our studies demonstrated that SLC31A1/copper suppression could enhance TAM responses for chemoresistant ER-positive breast cancer cells through constraining the CPT1A-mediated FAO process.